A Multifunctional Radiotheranostic Agent for Dual Targeting of Breast Cancer Cells. (30th June 2017) - Vultos, Filipe; Fernandes, Célia; Mendes, Filipa; Marques, Fernanda; Correia, João D. G.; Santos, Isabel; Gano, Lurdes
Abstract: A straightforward synthetic route for a new multifunctional 1, 4, 7, 10‐tetraazacyclododecane‐1, 4, 7, 10‐tetraacetic acid (DOTA) derivative is described. To demonstrate the versatility of this pro‐chelator for the preparation of radiolabeled hybrid compounds containing two different biological targeting moieties, an antitumor agent (e.g., a DNA‐intercalating agent) and an estrogen receptor (ER) ligand (e.g., LXXLL‐based peptide) were regiospecifically conjugated to the DOTA derivative. The bifunctional probe was radiolabeled with the auger electron emitter indium‐111, and the resulting radioconjugate was demonstrated to induce DNA damage in vitro, which, along with the nuclear internalization exhibited in breast cancer cells, might enhance its therapeutic activity. This favorable in vitro performance suggests that these hybrid compounds could be attractive probes for theranostic applications. Abstract : Taking an auger to cancer ! New bifunctional DOTA‐based pro‐chelator is described. As proof of concept, a dual‐vectorized conjugate was constructed that consists of two molecular entities with different targeting abilities: an antitumor agent (a DNA‐intercalator) and an estrogen‐receptor‐targeting peptide. Radiolabeling of the dual probe with indium‐111 generated a radioconjugate capable of reaching the nuclei of breast cancer cells and effectively inducing DNA damage in vitro.